La estrategia clínica matemática en el aprendizaje del cálculo en estudiantes del primer semestre de comercio internacional - Edgar Mauricio Perozo-León; Jhan Piero Rojas-Suarez; Martha Cecilia Santiago Carrillo (Mundo Fesc)
This article presents the results of a study titled "Influence of the Clinical Mathematical Strategy on the Advising and Learning of Calculus in International Trade Students." The objective of the study was to assess the influence of the strategy on the advising and learning of calculus among first-semester International Trade students at a university in Cúcuta. A quantitative methodology was used for its development. Data was collected through a knowledge test consisting of 25 multiple-choice, single-answer questions, administered both at the beginning and end of the process. The Honey Alonso test was also used to identify participants' learning styles. Finally, a satisfaction survey was administered to understand how the strategy impacted the study group. Data analysis included the calculation of the mean, mode, and median statistics. Bar charts and box-and-whisker graphs were also used. The nonparametric Wilcoxon rank test was used for hypothesis testing. The strategy was found to be effective and enhanced the participants' mathematical knowledge. The group was also motivated and showed a high level of satisfaction.